2018
DOI: 10.1007/s11367-018-1504-2
|View full text |Cite|
|
Sign up to set email alerts
|

An LCA of the Pelamis wave energy converter

Abstract: Purpose To date, very few studies have attempted to quantify the environmental impacts of a wave energy converter, and almost all of these focus solely on the potential climate change impacts and embodied energy. This paper presents a full life cycle assessment (LCA) of the first-generation Pelamis wave energy converter, aiming to contribute to the body of published studies and examine any potential trade-offs or co-benefits across a broad range of environmental impacts. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 20 publications
5
63
0
1
Order By: Relevance
“…Geographical distribution of the selected LCA studies, as shown in Table 1, indicates that 11 systems are installed in European seas [3,9,11,[13][14][15][16][17][18][19]22,23], 1 in New Zealand [12], 1 in China [20] and 1 in multicontinental locations [22]; three are located at hypothetical offshore locations [4,21,24].…”
Section: Spatial Distribution Of Studied Wave and Tidal Energy Systemsmentioning
confidence: 99%
See 4 more Smart Citations
“…Geographical distribution of the selected LCA studies, as shown in Table 1, indicates that 11 systems are installed in European seas [3,9,11,[13][14][15][16][17][18][19]22,23], 1 in New Zealand [12], 1 in China [20] and 1 in multicontinental locations [22]; three are located at hypothetical offshore locations [4,21,24].…”
Section: Spatial Distribution Of Studied Wave and Tidal Energy Systemsmentioning
confidence: 99%
“…As shown in Figure 1, the selected literature studied two oscillating surge WECs [22,25], one oscillating water column [21], three attenuators [14][15][16][17], two overtopping [3,23], four point absorbers [4,19,20,22], one vertical axis tidal [9], eight horizontal axis tidal [11][12][13]25], one Archimedes [13] and one tidal range [25].…”
Section: Spatial Distribution Of Studied Wave and Tidal Energy Systemsmentioning
confidence: 99%
See 3 more Smart Citations